Recursos en internet sobre prevención y resolución de conflictos, análisis internacional y cultura de paz - Val de Santos, María Elena (Revista Española de Desarrollo y Cooperación, 2023)
When we search for information about conflicts we found an amalgam of different sort of news. The next pages offer a group of net links to analyze and comprehend crisis, violent conflicts and wars all around the world in its full complexity and scope.